Cryptosporidium parvum prevalence in a group of Turkish children - Akyön, Yakut; Ergüven, Sibel; Arıkan, Sevtap; Yurdakök, Kadriye; Günalp, Ayfer (The Turkish Journal of Pediatrics, 1999)
Stool samples from two hundred children with diarrhea and from 50 healthy children were examined, by modified Kinyoun’s acid-fast staining (MAF), Giemsa staining and direct (DFA) and indirect immunofluorescence antibody (IFA) methods, in order to determine cryptosporidiosis prevalence under the age of 12 and to detect the most efficient identifying method for use in our country. Cryptosporidium oocysts were detected in seven (3.5%) of the cases. None of the samples from the control subjects was found to be positive for Cryptosporidium. Our results indicate that Cryptosporidial oocysts should be detected in children with diarrhea. Modified Kinyoun staining method is practical and reliable for this purpose. Immunofluorescence staining methods can be applied for conformation of the results, if available.